Applying OOK modulation in OFDM to reduce the ICI due to CFO and IQ imbalance. (15th October 2008) - Ma, Chuanhui; Atkin, Guillermo E.; Zhou, Chi
Orthogonal frequency division multiplexing (OFDM) has become one of the promising technologies for the next-generation communications systems to support high-speed high-quality digital transmission and reception. However, conventional OFDM systems are sensitive to both the carrier frequency offset (CFO) and in-phase and quadrature (IQ) imbalance, which cause the inter-carrier interference (ICI) among sub-carriers and greatly degrade the system performance. In this paper, we propose to apply on-off-keying (OOK) modulation in OFDM to reduce the ICI caused by those two factors. The analysis of symbol error rate (SER) is provided. Simulation results show that when the ICI resulting from both the CFO and IQ imbalance is significant, the proposed OFDM system outperforms a conventional OFDM system in terms of the SER due to the ICI reduction resulting from the imposed OOK modulation.